2010
DOI: 10.2337/db09-1694
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Monocyte Adhesion to Endothelial Cells and Attenuation of Atherosclerotic Lesion by a Glucagon-like Peptide-1 Receptor Agonist, Exendin-4

Abstract: OBJECTIVEExogenous administration of glucagon-like peptide-1 (GLP-1) or GLP-1 receptor agonists such as an exendin-4 has direct beneficial effects on the cardiovascular system. However, their effects on atherosclerogenesis have not been elucidated. The aim of this study was to investigate the effects of GLP-1 on accumulation of monocytes/macrophages on the vascular wall, one of the earliest steps in atherosclerogenesis.RESEARCH DESIGN AND METHODSAfter continuous infusion of low (300 pmol · kg−1 · day−1) or hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
381
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 473 publications
(408 citation statements)
references
References 38 publications
21
381
1
5
Order By: Relevance
“…Two previous reports have implied that GLP-1 analogues might exert anti-inflammatory properties [16,17]. One of them showed that exendin-4 inhibited interleukin-1β-induced inducible nitric oxide synthase at the protein level in RINm5F beta-cells [16].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Two previous reports have implied that GLP-1 analogues might exert anti-inflammatory properties [16,17]. One of them showed that exendin-4 inhibited interleukin-1β-induced inducible nitric oxide synthase at the protein level in RINm5F beta-cells [16].…”
Section: Discussionmentioning
confidence: 97%
“…One of them showed that exendin-4 inhibited interleukin-1β-induced inducible nitric oxide synthase at the protein level in RINm5F beta-cells [16]. The other report demonstrated that exendin-4 inhibits monocyte adhesion to endothelial cells and attenuates atherosclerotic lesions in apolipoprotein E-deficient mice, in which exendin-4 suppressed NF-κB activation in macrophages [17]. In both reports, the antiinflammatory effect was reversed by cAMP inhibitor or a protein kinase A inhibitor, suggesting that this effect of GLP-1 analogues is mediated through the GLP-1 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Further cardioprotective effects, by means of increased coronary flow, 29 reduced myocardial infarct size, 33 and improved left ventricular function, have also been suggested by animal data. 30,34 Human mechanistic studies are consistent with these findings demonstrating an improvement in flow-mediated vasodilation in the postprandial state, 13 reduced infarct size in patients with ST-segment elevation myocardial infarction, 12,14 and an improvement in left ventricular ejection fraction in patients with heart failure. 35 These data together justify the conduct of a large-scale, adequately powered outcome trial testing for the superiority of a diabetes treatment regimen containing once-weekly exenatide on cardiovascular outcomes.…”
Section: Discussionsupporting
confidence: 61%
“…[7][8][9][10][11] In addition, further pleiotropic effects on the cardiovascular system, both through GLP-1 receptor-mediated and other mechanisms, have been suggested. 29 Studies in animal models suggest beneficial effects of GLP-1 on atherogenesis, by inhibiting the inflammatory response in macrophages and endothelial adhesion 30 and modulating endothelial function. 31,32 Further cardioprotective effects, by means of increased coronary flow, 29 reduced myocardial infarct size, 33 and improved left ventricular function, have also been suggested by animal data.…”
Section: Discussionmentioning
confidence: 99%
“…Besides its insulinotropic action, exendin-4 may also exert direct beneficial effects on endothelial function. Exendin-4 reduces macrophage adhesion to the endothelium, an early step in the formation of atherosclerotic plaques and endothelial dysfunction (Arakawa et al 2010). Acute administration of exendin-4 in humans prevents endothelial dysfunction induced by ischemia reperfusion injury (Ha et al 2011) and after a high-fat meal load (Koska et al 2010), effects suggested to be GLP1 receptor and NO dependent (Nyström et al 2004).…”
Section: Introductionmentioning
confidence: 99%